Transmissão indutiva de energia eletromagnética sem fios, para aplicações em postos de abastecimento de veículos elétricos puros: modelação para o elemento eletromagnético - Jorgetto, Marcus Felipe Calori [UNESP] (2015)
This work proposes a modeling, design methodology and shows the main simulation results to the development of a Wireless Power Transmission (WPT) element, applied to pure Electric Vehicles (EV). The proposed structure is composed of at least two inductors, composing a transmitter and an energy receiver with weak magnetic coupling among them, considering a far-field energy-transfer method. Considering a literature review for the structures of the systems used for Wireless Power Transmission (WPT), it was observed the use of cylindrical spiral or square shapes, predominantly, in order to compose the inductive elements for power transmission. In this context, this work was based only on inductors with cylindrical spiral shape, which was analyzed based on electromagnetism theories. The proposed methodology starts from the Biot Savart Law and the Third Maxwell Law, in order to obtain the key design parameters for the inductive power transfer element (IPT - Inductive Power Transfer), which are: Mutual Inductance (transmitter / receiver), Self Inductance (transmitter) and Coupling Factor (transmitter / receiver). In order to prove the accuracy of the developed theoretical methodology, was adopted a computational model using the Comsol® software, considering a physical model for the designed IPT element. The results obtained from the proposed theoretical modeling are original and this is a pioneering work in determining algebraically a calculation method for mutual coupling between cylindrical spiral inductors that, when compared with the simulation results obtained by Comsol®, demonstrated practically exact. Furthermore, considering the application in a small-scale case study to WPT, for a pure Electric Vehicle (EV), an important contribution presented in this work is the analysis of arrangements for the inductive element of power transmitter, presenting its advantages and disadvantages and the best configuration for the case study. It should ...